2005
DOI: 10.1210/jc.2005-1366
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Skewed X-Chromosome Inactivation in Females with Autoimmune Thyroid Disease: A Possible Explanation for the Female Predisposition to Thyroid Autoimmunity

Abstract: These observations suggest a possible role of XCI in the etiology of AITD and may in part explain the female preponderance of AITD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
122
5
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(143 citation statements)
references
References 36 publications
12
122
5
4
Order By: Relevance
“…[11][12][13] In accordance with these studies, we found a statistically significant positive association between XCI and the serum concentrations of TPOAb in euthyroid subjects (within-cohort analysis). To evaluate whether this association was causal or could be explained by the presence of genetic or environmental confounders, we also analysed the association between XCI and TPOAb within MZ and DZ pairs.…”
Section: Discussionsupporting
confidence: 90%
“…[11][12][13] In accordance with these studies, we found a statistically significant positive association between XCI and the serum concentrations of TPOAb in euthyroid subjects (within-cohort analysis). To evaluate whether this association was causal or could be explained by the presence of genetic or environmental confounders, we also analysed the association between XCI and TPOAb within MZ and DZ pairs.…”
Section: Discussionsupporting
confidence: 90%
“…These endocrine problems may be related to direct RNA toxicity in the hypothalamic-pituitary axis, or to a direct effect of RNA toxicity on the thyroid-perhaps through an autoimmune mechanism or the induction of apoptosis in the thyroid cells. A skewed AR has been previously reported in patients with thyroid problems related to autoimmune disease [Brix et al, 2005;Ozcelik et al, 2006], but in this study there was no difference in the AR between those with and without thyroid disease. Surprisingly, there was also no difference in the AR in females with and without FXTAS.…”
Section: Discussioncontrasting
confidence: 66%
“…Using disease discordant twin pairs, Brix and collaborators have found that the frequency of skewed X chromosome inactivation in female twins with HT was 31% (vs 8% in control population) (Brix et al, 2005). In Tunisian population, findings reported by our team suggest a possible role for X chromosome inactivation mosaicism in the pathogenesis of AITDs (GD and HT) and may, to some extent, explain the female preponderance of these diseases (Chabchoub et al, 2009).…”
Section: Epigenetic Factorssupporting
confidence: 49%